PENINGKATAN KOMPETENSI PENGELOLA ARSIP DENGAN KEAHLIAN DOKUMEN FORENSIK - Achmad Fachmi (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2023)
This research examines the increase in the capacity of record managers in organizations, and this is because the record management profession has a strategic role in the organization, thus making record managers a profession that is vulnerable to legal problems because it is directly related to valid evidence, namely records. For this reason, it is necessary to increase competence, one of which is competence in forensic documents. This competency is closely related and becomes a distinct advantage for record managers because document forensic activities examine and involve the record itself. The method used in this research is a literature study using reference sources of articles in journals, books, laws, and literature on websites. Literature sources are used to develop critical thinking and aspects related to increasing the competency of record managers with forensic document expertise. The results of the discussion show that record managers must improve their capabilities and abilities due to the demands of the times and their role and involvement in legal matters within the organization. Increasing competence has an impact on increasing the welfare and value of record managers. For this reason, a new framework is needed for the record management profession, namely the competency of forensic documents. This competency is very closely related because forensic document competency is an activity that examines and involves the record itself.